ANALYSIS OF DANIEL PLAINVIEW’S CHARACTER TRAITS IN THE MOVIE “THERE WILL BE BLOOD” BY PAUL THOMAS ANDERSON - Abdul Muhid Murtadho; Eka Supriatna; Suhendar Suhendar (STIBA IEC JAKARTA, 2021)
The objective of this research is to analyze about three important aspects, as the component of the story which are related to each other and also as the element of literature. The writer defines about Daniel Plainview’s character traits that his negative character traits are related to the factor of several conflicts in the story. The story depicts of his ambition, persistence, greed and hatred. Ambition and persistence influenced to his success achievement as the oilman, while his greed and hatred are related to the factor of several conflicts in the story. The second aspect is to identify some people who involved in conflicts with Daniel Plainview in the story and the third aspect is to define moral values reflection from the story as a wisdom and life learning for the writer or for the readers. The writer applies content analysis which is the part of qualitative research. This research found that (1) the negative character traits are related to several conflicts and (2) moral values reflection defined as the generosity that as the opposite of greed which is depicted obviously from the main character.